The Influence of Family Ties on Men's Prostate Cancer Screening, Biopsy, and Treatment Decisions. (November 2013) - Shaw, Eric K.; Scott, John G.; Ferrante, Jeanne M.
Extensive research has focused on understanding family dynamics of men with prostate cancer. However, little qualitative work has examined the role of family ties on men's prostate cancer decisions across the spectrum of screening, diagnosis, and treatment. Using data from a larger study, we qualitatively explored the influence of family ties on men's prostate cancer decisions. Semistructured interviews were conducted with men ages ≥50 ( N = 64), and data were analyzed using a grounded theory approach and a series of immersion/crystallization cycles. Three major themes of spousal/family member influence were identified: (a) spousal/family member alliance marked by open communication and shared decision making, (b) men who actively opposed spouse/family member pressure and made final decisions themselves, and (c) men who yielded to spouse/family member pressure. Our findings provide insights into men's relational dynamics that are important to consider for the shared decision-making process across the prostate cancer spectrum.